الأهمية التشخيصية لخزعة الإبرة الارتشافية الدقيقة في تشخيص أورام الرأس والعنق. (خبرة مشفى الأسد الجامعي في اللاذقية بين عامي 2012-2013) - العلوني, فايز; يوسف, يوسف; ضومط, مي (Latakia University Journal -Medical Sciences Series, 2014)
شملت الدراسة50 مريضاً راجعوا قسم الأذنية في مشفى الأسد الجامعي في اللاذقية بين عامي 2012و2013. أجري لهم خزعة بالإبرة الارتشافية الدقيقة (FNA) لكتل في الرأس والعنق . نتائج الفحص الخلوي للFNA كانت على الشكل التالي : 14 حالة التهابية أي بنسبة 28% , 32 حالة ورمية أي بنسبة 64 % ( منها12 حالة خبيثة و 20 حالة سليمة ) , 4 حالات غير نوعية أي بنسبة 8% . بالمقارنة مع نتائج التشريح المرضي النهائي كانت هناك حالة إيجابية كاذبة وثلاث حالات سلبية كاذبة. التشخيص النهائي : 15 حالة التهابية أي بنسبة 30 % 35 حالة ورمية أي بنسبة 70% حساسية ال FNA84,3 % و النوعية 88,8 % لم تحدث اختلاطات للFNA . Thos study included 50 patients who were admitted to the Department of Otolaryngology at Al-Assad University Hospital in Lattakia between 2012 and 2013. Fine needle aspiration biopsy (FNA) was conducted on the patients for head and neck masses. Results of FNA cytology were as the follows: 14 Inflammatory cases that rate 28 %. 32 tumor cases that rate 64 % ( 12 malignant cases , 20 benign cases). 4 cases were not indicative that rate 8%. Compared with the results of the final histopathology, there was one case of false positive and three cases of false negative. Final diagnosis: 15 Inflammatory cases that rate 30 %. 35 tumor cases that rate 70 %. The sensitivity of FNA was 84.3 %, and specificity was 88,8 %. There were not any complications of FNA.